#### Answer

$x^{2}$-26x+169

#### Work Step by Step

$(x-13)^{2}$=
=$x^{2}$-(2)(x)(13)+$13^{2}$=
$x^{2}$-26x+169

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$x^{2}$-26x+169

$(x-13)^{2}$=
=$x^{2}$-(2)(x)(13)+$13^{2}$=
$x^{2}$-26x+169

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.